Congenital Prepapillary Arterial Convolutions: A Requiem for William F. Hoyt. (September 2020) - Brodsky, Michael C.
Abstract : Abstract: This vignette describes a diagnostic telephone consultation with Bill Hoyt regarding a 65-year-old man who was found to have an unusual vascular pattern overlying the left optic disc. Bill recognized and characterized this condition as prepapillary arterial convolutions, a congenital vascular anomaly that has never entered the scientific literature. Close inspection disclosed evidence of mild vascular derangement in the contralateral eye as well. The cause of this condition remains unknown.